SARS‐CoV‐2 can be detected in urine, blood, anal swabs, and oropharyngeal swabs specimens. Issue 9 (30th April 2020) - Peng, Liang; Liu, Jing; Xu, Wenxiong; Luo, Qiumin; Chen, Dabiao; Lei, Ziying; Huang, Zhanlian; Li, Xuejun; Deng, Keji; Lin, Bingliang; Gao, Zhiliang
Abstract: Purpose: The purpose of this study was to detect severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) ribonucleic acid (RNA) in urine and blood specimens, and anal and oropharyngeal swabs from patients with confirmed SARS‐CoV‐2 infection, and correlated positive results with clinical findings. Methods: Patients with confirmed SARS‐CoV‐2 infections were included in this study. Patients' demographic and clinical data were recorded. Quantitative real‐time polymerase chain reaction was used to detect SARS‐CoV‐2 RNA in urine and blood specimens, and anal and oropharyngeal swabs. The study is registered at ClinicalTrials.gov (No. NCT04279782, 19 February, 2020). Results: SARS‐CoV‐2 RNA was present in all four specimen types, though not all specimen types were positive simultaneously. The presence of viral RNA was not necessarily predictive of clinical symptoms, for example, the presence of viral RNA in the urine did not necessarily predict urinary tract symptoms. Conclusions: SARS‐CoV‐2 can infect multiple systems, including the urinary tract. Testing different specimen types may be useful for monitoring disease changes and progression, and for establishing a prognosis. Highlights: SARS‐CoV‐2 can be detected in multiple system specimens but without necessarily corresponding dysfunction. Further study is needed to determine the virus ability to destroy different organs.